The Protection of the Fundamental Procedural Rights of Business Entitiesby Applying Sanctions and the Results of the Legal Systematization of These Rights - Pogužinskė, Eimantė (Teisė, 2021)
The present article analyses the extent of influence the adopted Article of the Law on Public Administration of the Republic of Lithuania (Art. 368, currently Art. 37), which systematises the basic procedural rights of business entities, has on the protection of business entities’ procedural rights, which are assured by the Supreme Administrative Court of Lithuania in its case law. The precise provisions invoked as basis for procedural rights protection in the case law of the Supreme Administrative Court of Lithuania regarding sanctions imposed on business entities are showcased. Furthermore, the results and plausible reasons for the application or non-application of procedural rights systematized in the Law on Public Administration are appraised.
Keywords: business entity; sanctions; supervision; procedural rights; principle of good administration; right of defence